Systematic morphology, anatomy and numerical evaluation of Clerodendrum L.in Peninsular Malaysia - Mazatul Azrin Rahman (Tanjong Malim, 2018)
Systematic morphology, anatomy and numerical evaluation of Clerodendrum L.in Peninsular Malaysia by Mazatul Azrin Rahman